Potensi Bakteri Asam Laktat yang Diisolasi dari Dadih untuk Menurunkan Kadar Kolesterol Darah - Usman Pato (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2004)
Epidemiological, laboratory and clinical studies have shown a good correlation between high serum cholesterol and increased risk for the incidence of coronary heart disease. Reduction in total cholesterol and LDL cholesterol in hypercholesterolemic men reduces the incidence of cardiovascular disease. Modification of diets such as ingestion of probiotic in the form offermented foods or lactic acid bacteria-containing foods is considered as a more natural way to decrease serum cholesterol in humans. Lactic acid bacteria isolated from dadih could reduce the total cholesterol and LDL cholesterol levels in hypercholesterolemic rats by deconjugation of bile salts. Deconjugation of bile salts by BSH of dadih LAB resulted in an increased production of deconjugated bile acids. Deconjugated bile acids are less well absorbed from the small intestine than the conjugated bile acids. Thus, the amount of bile acids returned to the liver during enterohepatic circulation decreased. Deconjugated bile acids are also excreted more rapidly than conjugated bile acids and they bind more easily to the dietary fiber and intestinal bacteria than conjugated bile acids. Loss of bile acids may indeed result in an increased requirement of cholesterol as a precursor for the synthesis of new bile acids. As a consequence, the total cholesterol levels in the body were decreased